Evaluation of Probiotic and Antidiabetic Attributes of Lactobacillus Strains Isolated From Fermented Beetroot - Kumari, V. B. Chandana; Huligere, Sujay S.; Ramu, Ramith; Naik Bajpe, Shrisha; Sreenivasa, M. Y.; Silina, Ekaterina; Stupin, Victor; Achar, Raghu Ram (Frontiers in Microbiology, 2022)
Fermented foods are sources of functionally salient microbes. These microbes when ingested can regulate biomolecule metabolism which has a plethora of health benefits. Lactic acid bacteria species (LABs) isolated from fermented beetroot were biochemically characterized and validated using 16s rRNA sequence. Also, an in vitro assay was conducted to confirm the probiotic activity of the isolates. The cell-free supernatant (CS), cell-free extract (CE), and intact cell (IC) were evaluated for α-glucosidase and α-amylase inhibition. The six isolates RAMULAB01–06 were categorized to be Lactobacillus spp. by observing phenotypic and biochemical characters. Molecular validation using 16S rDNA sequencing, followed by homology search in NCBI database, suggested that the isolates are >95% similar to L. paracasei and L. casei. Also, isolates exhibited probiotic potential with a high survival rate (>96%) in the gastrointestinal condition, and adherence capability (>53%), colonization (>86%), antibacterial, and antibiotic activity. The safety assessments expressed that the isolates are safe. The α-glucosidase and α-amylase inhibition by CS, CE, and IC ranged from 3.97 ± 1.42% to 53.91 ± 3.11% and 5.1 ± 0.08% to 57.15 ± 0.56%, respectively. Hence, these species have exceptional antidiabetic potential which could be explicated to its use as a functional food and health-related food products.